2007
DOI: 10.1021/cm0623110
|View full text |Cite
|
Sign up to set email alerts
|

Quadratic Nonlinear Optical Response in Partially Charged Donor-Substituted Tetrathiafulvalene:  From a Computational Investigation to a Rational Synthetic Feasibility

Abstract: A computational (ZINDO) investigation is employed to estimate the molecular hyperpolarizability (β) of a [(TTF−NH2)8] (TTF = tetrathiafulvalene) octameric stack at various fractional (0 < ρ < 1) oxidation states of TTFρ+. While the neutral [(TTF−NH2)8] octamer exhibits a modest (7.6 × 10-30 cm5 esu-1) static β0 value, in relation to a nearly centrosymmetric electronic structure, the formal (TTF−NH2)0.25+ oxidation state leads to a giant (β0 = 3891 × 10-30 cm5 esu-1 per octamer) NLO response. This effect is rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 63 publications
1
16
0
Order By: Relevance
“…A large contrast of the first hyperpolarizability has also been combined with other mechanisms of commutation, in particular, those based on redox or protonation/deprotonation reactions. Reversible redox‐switching NLO behaviors have been investigated in detail in Ru II ‐ and Fe II ‐based chromophores,8 as well as in substituted helicenes9 and in stacks of tetrathiafulvalene 10. In the case of commutations triggered by the pH, 6s‐ cis ‐retinal and its 13‐ cis isomer,11 as well as pyridine‐based octupolar systems12 have shown large β contrasts.…”
Section: Introductionmentioning
confidence: 99%
“…A large contrast of the first hyperpolarizability has also been combined with other mechanisms of commutation, in particular, those based on redox or protonation/deprotonation reactions. Reversible redox‐switching NLO behaviors have been investigated in detail in Ru II ‐ and Fe II ‐based chromophores,8 as well as in substituted helicenes9 and in stacks of tetrathiafulvalene 10. In the case of commutations triggered by the pH, 6s‐ cis ‐retinal and its 13‐ cis isomer,11 as well as pyridine‐based octupolar systems12 have shown large β contrasts.…”
Section: Introductionmentioning
confidence: 99%
“…Apparently, the ground state On the microscopic level, the center conjugated framework of the present systems ensures that the molecular structure has good thermal stability. π-π bowl interactions between molecules in-line in a head-to-tail arrangement along the dipole direction can produce a very strong cohesive coupling among electric dipoles and favor an intermolecular efficient channel for charge transport 36,[71][72][73] . Appropriate choices of the length, composition of branches and introduction of doping atoms in the central core to change its oxidation/reduction ability allow us to design molecules with optimal trade-off between hyperpolarizability and optical transparency [61][62][63][64][65][66] .…”
Section: Resultsmentioning
confidence: 99%
“…Such materials possess large optical windows in the near-infrared domain compatible with electro-optical applications. We have also suggested from a computational investigation that extremely large ˇ values could be obtained in the case of metallic conductivity, when fractional oxidation states are present [58]. Although the resulting materials are strongly absorbent over a large frequency domain, which prohibits their use in most current optical applications, we have reported that their experimental NLO efficiencies could be extremely large on particles of size range of few m 3 [59].…”
Section: Molecular Materials Combining Conducting and Nlo Propertiesmentioning
confidence: 89%